The effect of finacial performance, devidend policy on the firm value with corporate social responsibility (CSR) as moderating variable - Vica Prahelga (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2024)
Abstract This study investigates the impact of capital structure, profitability, leverage, and dividend policy on company value, focusing on how corporate social responsibility (CSR) moderates these relationships. The research was conducted on financial services companies in the banking sub-sector listed on the Indonesia Stock Exchange from 2019 to 2023. The sampling method used was purposive sampling, resulting in 16 companies meeting the criteria for analysis. Secondary data from each sample company's official website or www.idx.co.id was used. The data was analyzed using descriptive statistics, classic assumption tests, normality, heteroscedasticity, multicollinearity tests, model selection tests, panel data regression analysis, hypothesis tests, and moderated regression analysis (MRA) tests. Eviews Software Version 12 was used for data processing. The findings suggest that capital structure, profitability, leverage, and dividend policy positively and significantly impact company value. Additionally, the moderated regression analysis (MRA) results indicate that CSR plays a moderating role in the relationship between these financial factors and company value. Public interest statements This research emphasizes the importance of capital structure, profitability, and dividend policy in determining company value. It provides valuable insight for investors and consumers into a company's financial management and decision-making, enabling informed investment choices and employment decisions.